Long-Term Lithium Treatment Increases cPLA(2) and iPLA(2) Activity in Cultured Cortical and Hippocampal Neurons - De-Paula, Vanessa de Jesus (Molecules, 2015)
Background: Experimental evidence supports the neuroprotective properties of lithium, with implications for the treatment and prevention of dementia and other neurodegenerative disorders. Lithium modulates critical intracellular pathways related to neurotrophic support, inflammatory response, autophagy and apoptosis. There is additional evidence indicating that lithium may also affect membrane homeostasis. Objective: To investigate the effect of lithium on cytosolic phospholipase A(2) (PLA(2)) activity, a key player on membrane phospholipid turnover which has been found to be reduced in blood and brain tissue of patients with Alzheimer’s disease (AD). Methods: Primary cultures of cortical and hippocampal neurons were treated for 7 days with different concentrations of lithium chloride (0.02 mM, 0.2 mM and 2 mM). A radio-enzymatic assay was used to determine the total activity of PLA(2) and two PLA(2) subtypes: cytosolic calcium-dependent (cPLA(2)); and calcium-independent (iPLA(2)). Results: cPLA(2) activity increased by 82% (0.02 mM; p = 0.05) and 26% (0.2 mM; p = 0.04) in cortical neurons and by 61% (0.2 mM; p = 0.03) and 57% (2 mM; p = 0.04) in hippocampal neurons. iPLA(2) activity was increased by 7% (0.2 mM; p = 0.04) and 13% (2 mM; p = 0.05) in cortical neurons and by 141% (0.02 mM; p = 0.0198) in hippocampal neurons. Conclusion: long-term lithium treatment increases membrane phospholipid metabolism in neurons through the activation of total, c- and iPLA(2). This effect is more prominent at sub-therapeutic concentrations of lithium, and the activation of distinct cytosolic PLA(2) subtypes is tissue specific, i.e., iPLA(2) in hippocampal neurons, and cPLA(2) in cortical neurons. Because PLA(2) activities are reported to be reduced in Alzheimer’s disease (AD) and bipolar disorder (BD), the present findings provide a possible mechanism by which long-term lithium treatment may be useful in the prevention of the disease.